Teachers’ Perceptions on the Effectiveness of DepEd TV and Radio-Based Instruction in Teaching Mathematics Among Teachers in Cawayan East District - Amistoso, Richelle Marie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of DepEd TV and Radio-Based Instruction as alternative learning modalities in teaching Mathematics during the pandemic. Guided by the Department of Education’s implementation of distance learning, the study aimed to determine teachers’ perceptions regarding the accessibility, instructional delivery, and overall effectiveness of these broadcast-based modalities. A descriptive research design was utilized, employing survey questionnaires as the primary instrument for data gathering. The respondents of the study were Mathematics teachers involved in the implementation of DepEd TV and Radio-Based Instruction. Data were analyzed using appropriate statistical tools to determine the respondents’ perceptions and the challenges encountered in the implementation process. Findings revealed that DepEd TV and Radio-Based Instruction contributed significantly to the continuity of Mathematics education, especially among learners with limited internet connectivity and access to digital devices. Teachers perceived these modalities as beneficial in supporting lesson delivery and learner access to educational content. However, several challenges affected the effectiveness of implementation, including poor signal reception, unstable electricity supply, limited availability of devices, and low learner engagement. The study also found that teachers’ professional background and teaching experience influenced their perceptions of the effectiveness of the modalities. Based on the findings, the study concluded that broadcast-based instruction remains a valuable alternative learning strategy but requires strengthened technical, infrastructural, and instructional support to improve educational outcomes. The study supports Sustainable Development Goal (SDG) 4: Quality Education by promoting inclusive and accessible learning opportunities during emergencies and disruptions in traditional schooling. It also contributes to sustainable educational practices by strengthening alternative learning systems that support equitable access to education in underserved communities. The sustainability impact of the study lies in its potential to guide institutional policies and educational interventions that enhance resilience, accessibility, and continuity in basic education delivery.